Melodramatic Codes Applied to the Lovers in the Play Do Fundo do Baú (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article analyzes the performance Do Fundo do Baú, by the company Os Mascaratis, investigating how melodramatic codes intersect with commedia dell’arte in the construction of the lovers. The study adopts a qualitative approach and a creative process analysis, engaging with the works of Thomasseau, Tiche Vianna, and Lecoq. In the lovers, lyricism and the ridiculous intertwine, revealing tensions between melodramatic solemnity and farcical comedy. It is concluded that the vitality of these languages lies in their capacity for reinvention in new scenic contexts.
Keywords: Commedia dell’Arte; lovers; melodrama